The performance of Islamic and conventional microfinance loans in Afghanistan: The Taliban and beyond - Mustafa Disli (17307716) (2024)
The Afghanistan microfinance industry has witnessed laurels in recent decades, making it crucial to closely monitor its development and sustainability. This study aims to assess the performance of Islamic and conventional microfinance loans in two aspects: first, by examining the occurrence of loan defaults, and second, by distinguishing between loan performance in areas controlled by the Taliban and those outside their control. To accomplish this, we analyze a unique dataset comprising over 9500 borrowers linked to an Afghan microfinance institution during the period spanning from January 2017 to February 2020. Our findings reveal that regions under Taliban control experienced fewer instances of loan defaults compared to areas not under their influence. Additionally, our analysis indicates that borrowers of Islamic loans in Afghanistan default more frequently than borrowers of conventional loans, particularly in Taliban-controlled areas. These observations remain largely consistent when we explore the factors influencing the number of days overdue on loan repayments. Furthermore, our conclusions find further support from both of the microfinance institution's Islamic loan products: business Murabaha loans, available to individuals of any gender, and women Murabaha loans, created as a group lending scheme exclusively for women. The results from this study offer valuable insights into how policy discussions in Afghanistan should be adjusted to facilitate a smooth transition for the microfinance industry. Other Information Published in: Emerging Markets Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ememar.2023.101104 Additional institutions affiliated with: Islamic Finance and Economy Program - CIS